Increased diagnostic yield in a cohort of hearing loss families using a comprehensive stepwise strategy of molecular testing - Zeng, Beiping; Xu, Hongen; Yu, Yanan; Li, Siqi; Tian, Yongan; Li, Tiandong; Yang, Zengguang; Wang, Haili; Wang, Guangke; Chang, Mingxiu; Tang, Wenxue (Frontiers in Genetics, 2022)
Hearing loss is one of the most common sensory disorders in humans. This study proposes a stepwise strategy of deafness gene detection using multiplex PCR combined with high-throughput sequencing, Sanger sequencing, multiplex ligation-dependent probe amplification (MLPA), and whole-exome sequencing (WES) to explore its application in molecular diagnosis of hearing loss families. A total of 152 families with hearing loss were included in this study, the highest overall diagnosis rate was 73% (111/152). The diagnosis rate of multiplex PCR combined with high-throughput sequencing was 52.6% (80/152). One families was diagnosed by Sanger sequencing of GJB2 exon 1. Two families were diagnosed by MLPA analysis of the STRC gene. The diagnosis rate with additional contribution from WES was 18.4% (28/152). We identified 21 novel variants from 15 deafness genes by WES. Combining WES and deep clinical phenotyping, we diagnosed 11 patients with syndromic hearing loss (SHL). This study demonstrated improved diagnostic yield in a cohort of hearing loss families and confirmed the advantages of a stepwise strategy in the molecular diagnosis of hearing loss.